Automotive Systems Engineering II - Winner, Hermann; Prokop, Günther; Maurer, Markus; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book is the second volume reflecting the shift in the design paradigm in automobile industry. It presents contributions to the second and third workshop on Automotive Systems Engineering held in March 2013 and Sept. 2014, respectively. It describes major innovations in the field of driver assistance systems and automated vehicles as well as fundamental changes in the architecture of the vehicles.
Design of ride comfort characteristics on subsystem level in the product development process -- Methods for Change Management in Automotive Release Processes -- Increasing energy-efficient driving using uncertain online data of local traffic management centers -- Modelling logical architecture of mechatronic systems and its quality control -- Functional System Architecture for an Autonomous On-Road Motor Vehicle -- Towards a system-wide functional safety concept for automated road vehicles -- A Method for an Efficient, Systematic Test Case Generation for Advanced Driver Assistance Systems in Virtual Environments -- Validation and Introduction of Automated Driving.
Keywords: Automotive engineering; Engineering design; User interfaces (Computer systems).; Human-computer interaction; Technological innovations; Automotive Engineering; Engineering Design; User Interfaces and Human Computer Interaction; Innovation and Technology Management